Superfícies tridimensionais de energia pelo formalismo Hamiltoniano: aplicação no problema de estabilidade transitória em sistemas elétricos de potência - SILVA, Emanuelle do Carmo Machado da (2018)
This work develops an energy function designed to direct analysis of transient stability in electric power systems using Lyapunov stability criteria and the Hamiltonian formalism. The proposed energy function aims to identify the highlights and possible shortcomings of the Hamiltonian formalism to analyze the problem. It has been shown that the Hamiltonian function can also be treated as a energy function. To simplify and facilitate the understanding of the proposal, the classical model of synchronous generator was used for the development of the energy function, without any kind of control system. The proposal is tested in transient stability problems considering three different test systems, all subjected to action of an external force (fault). The possible stable and unstable states of the generators were built using the proposed energy function. The results are presented in the form of three-dimensional surfaces.